The effect of environmental influence on learning yoga to improve attention and concentration in learning disabled children. - Vijayalakshmi, P.; Ali Patel JM, Asgar (International Journal of Psychosocial Rehabilitation, 2024)
Environment influences the behaviour at different levels. These environments are included as social settings, built environments and informational environments. Learning Disability is a disorder in one or more of the fundamental psychological processes connected in comprehending the use of language, spoken and written. Apart from genetic factors, learning disability is influenced by various environmental factors. This study investigated the effect of environmental influence on learning yoga to improve attention and concentration in learning disabled children. This single blind randomized controlled trial was carried out among 55 children with learning abilities. The participants were divided into three groups, control group with 12 participants, experimental group I (without modified environment) with 24 participants and experimental group II (with modified environment) consisting of 19 participants. Intervention training program was given for three weeks, with 15 sessions. Letter cancellation test (1&2) and digit span test (Wechsler intelligence test) were used to measure the level of attention problem and to measure the level of concentration. There was a significant difference in attention and concentration for learning disabled children between pre and post scores in the experimental groups for both letter cancellation test and digit span test (P<0.05). The role of yoga in a controlled environmental setting plays a significant role in nurturing the learning abilities in children. This can be justified by incorporating yoga as a part of the school curriculum.